Review of Platyplastinx Enderlein, 1937 (Diptera, Psychodidae) with descriptions of four new species - Lopes, Priscila Silva; Bravo, Freddy (Zootaxa, 2015)
Platyplastinx Enderlein, with eight previously described species, is currently known to occur in the southeastern United States, Costa Rica, Ecuador and Brazil. Four new species from Brazil are described: Platyplastinx amazonensis sp. nov., P. duckhousei sp. nov., P. exiguus sp. nov. and P. hirsutus sp. nov. Platyplastinx obscurus (Bravo, Lago & Castro, 2004) comb. n. is transferred from Alepia. The generic diagnosis is updated, global species are listed, and an identification key for males of all species is provided. Thirteen species are now known, eight of which are described from Brazil.